Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1128/jb.00807-13
|View full text |Cite
|
Sign up to set email alerts
|

Residues in Conserved Loops of Intramembrane Metalloprotease SpoIVFB Interact with Residues near the Cleavage Site in Pro-σ K

Abstract: bIntramembrane metalloproteases (IMMPs) control critical biological processes by cleaving membrane-associated proteins within a transmembrane segment or at a site near the membrane surface. Phylogenetic analysis divides IMMPs into four groups. SpoIVFB is a group III IMMP that regulates Bacillus subtilis endospore formation by cleaving Pro-K and releasing the active sigma factor from a membrane. To elucidate the enzyme-substrate interaction, single-cysteine versions of catalytically inactive SpoIVFB and C-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 62 publications
5
54
0
Order By: Relevance
“…The observation that Y69C in the MRE β‐loop can be crosslinked to at least two different positions in the TM segment of RseA suggests a flexible nature for the RseP–substrate interaction, as suggested previously (Koide et al ., ; Zhang et al ., ). Obviously structural analysis of the RseP–substrate complex will be needed to understand the molecular details of the interaction between RseP and a substrate.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The observation that Y69C in the MRE β‐loop can be crosslinked to at least two different positions in the TM segment of RseA suggests a flexible nature for the RseP–substrate interaction, as suggested previously (Koide et al ., ; Zhang et al ., ). Obviously structural analysis of the RseP–substrate complex will be needed to understand the molecular details of the interaction between RseP and a substrate.…”
Section: Discussionmentioning
confidence: 97%
“…Structural analysis of mjS2P, an archaeal S2P homolog, showed that it has a b-hairpin-like-loop inserted from the cytoplasmic side into the membrane domain in the vicinity of the proteolytic active site (Feng et al, 2007). This bhairpin-like-loop is conserved among Group I and III S2P homologs, including E. coli RseP and B. subtilis SpoIVFB (Zhang et al, 2013;Akiyama et al, 2015). A study on SpoIVFB demonstrated that its b-hairpin-like-loop could be crosslinked with a substrate (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1C) is nonphysiological. SpoIVFB appears to have three short (3-to 8-residue) periplasmic loops (21) and BofA appears to have a short (31-residue) C-terminal periplasmic domain (27), based on analysis of PhoA fusion proteins expressed in E. coli and based on a homology model of SpoIVFB (28). In contrast, SpoIVFA appears to have a long (173-residue) C-terminal extracytoplasmic domain (21,29) and resisted cleavage by 2TM-RasP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1. Here, some additional features of RasP are depicted, including the HELGH motif with its catalytic E21 residue (9), a putative membrane-reentrant ␤-loop between TMS 1 and TMS 2 (28,50), a PSD-95/Dgl/ZO-1 (PDZ) domain between TMS 2 and TMS 3 (30), and a short loop interrupting TMS 3 that is predicted on the basis of the structure of a Methanocaldococcus jannaschii IMMP (51) and is followed by a conserved DG sequence whose D residue together with the two H residues of the HELGH motif are predicted to coordinate a zinc ion (30). The topology of RsiW was determined in B. subtilis (9) and is predicted to be the same in E. coli.…”
Section: Rasp Can Inhibit Coexpression Of Other Membrane Proteins In mentioning
confidence: 99%